2009
DOI: 10.1002/bate.200910038
|View full text |Cite
|
Sign up to set email alerts
|

Small‐strain stiffness in geotechnical analyses

Abstract: Nonlinear soil behaviour at small strains is often neglected in geotechnical analyses. Doing so often leads to an overestimation of foundation settlements and retaining wall deflections. Settlement troughs behind retaining walls or above tunnels, on the other hand, may be analysed as too flat and extended. Comparing measured displacements of piles or anchors within the working load range, to those calculated without considering small-strain stiffness, shows a considerably too soft response. This paper is conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 21 publications
0
23
0
1
Order By: Relevance
“…For more details of HS model, one can refer to [17,18]. For more details of HSS model, one can refer to [19,20]. The soil parameters used in this research are given in Table 2.…”
Section: Numerical Simulation Of Shield Supported Tunnelingmentioning
confidence: 99%
“…For more details of HS model, one can refer to [17,18]. For more details of HSS model, one can refer to [19,20]. The soil parameters used in this research are given in Table 2.…”
Section: Numerical Simulation Of Shield Supported Tunnelingmentioning
confidence: 99%
“…Here it is recommended that the model is combined with a hardening plasticity model, as, for example, done in the HS-Small model [8], where the smallstrain overlay model is combined with an isotropically hardened plasticity model. In [8] it is also shown that such a model combination applied to boundary value problems can not only improve the predictions of displacement fields but also minimize discretization errors.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3 shows the results of Equation (1) for a total of 32 parameter sets for different soils found in the literature. All references to the test data shown in Figure 3 are provided in [8], where a more complete overview of the parameters known to influence small-strain stiffness is also given.…”
Section: Small-strain Stiffnessmentioning
confidence: 99%
“…Hamrouni et al [38] highlighted the impact of soil constitutive models on the prediction of the displacements of the surrounding soil in the execution of a shallow tunnel. Benz et al [39] described soil stiffness at small-strains and presented the available smallstrain stiffness models. The authors also performed four numerical applications on: triaxial test, spread footing problem and excavation problem 2D and 3D, using the finite element method with and without small-strain stiffness formulation.…”
Section: Introductionmentioning
confidence: 99%